2020
DOI: 10.1101/2020.03.26.010322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-specific analysis of the SARS-CoV-2 glycan shield

Abstract: The emergence of the betacoronavirus, SARS-CoV-2 that causes COVID-19, represents a significant threat to global human health. Vaccine development is focused on the principal target of the humoral immune response, the spike (S) glycoprotein, that mediates cell entry and membrane fusion. SARS-CoV-2 S gene encodes 22 N-linked glycan sequons per protomer, which likely play a role in immune evasion and occluding immunogenic protein epitopes. Here, using a site-specific mass spectrometric approach, we reveal the gl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
183
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 40 publications
14
183
4
2
Order By: Relevance
“…Our findings are in line with those of previous studies, that demonstrated the predominant complex of N-glycans attached to MERS-CoV and SARS-CoV proteins (4,5,28). Moreover, two recent preprint studies have revealed that the complex N-glycans dominate the glycosites on human cell-expressed SARS-CoV-2 S protein (29,30). In contrast, S protein expression in insect cells led to a high ratio of high-mannose N-glycans ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with those of previous studies, that demonstrated the predominant complex of N-glycans attached to MERS-CoV and SARS-CoV proteins (4,5,28). Moreover, two recent preprint studies have revealed that the complex N-glycans dominate the glycosites on human cell-expressed SARS-CoV-2 S protein (29,30). In contrast, S protein expression in insect cells led to a high ratio of high-mannose N-glycans ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a glycomics analysis of influenza A virus produced in five different cell lines, all of relevance to vaccine production, let to the observation of profound differences in the compositions of the glycans at a given site; with structures varying from paucimannose (Sf9 cells) to core-fucosylated hybrid with bisecting N-acetylglucosamine (Egg) to sialylated biantennary glycans (HEK293) 18 . For these reasons, we have modeled the S glycoprotein with reported site-specific glycosylation 15 , as well as hypothetical homogeneously glycosylated glycoforms of the high mannose (M9), paucimannose (M3), biantennary complex (Complex) and core-fucosylated biantennary complex (Complex Core F) types. Comparisons among the glycoforms permits an assessment of the impact of cell-based differential glycan processing on S protein antigenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, a cryo-EM structure of the SARS-CoV-2 S glycoprotein has been reported 13 , which led to conclusion that, like the related protein from the 2002 -2003 SARS pandemic (SARS-CoV-1) 14 , the CoV-2 S protein is also extensively glycosylated 13 . Furthermore, an analysis of the glycan structures present at each glycosite in the S protein produced recombinantly in human embryonic kidney 293 cells has also been recently reported 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we show the presence of a distinct insert that maps to the S1/S2 priming loop of the SARS-CoV-2 spike protein and is not shared with SARS-CoV or any SARS-related viruses in Betacoronavirus lineage B. During the preparation of this manuscript, the cryo-electron microscopy structures of SARS-CoV-2 S have recently been determined [33,52,53]. These studies have revealed in detail the structure of the SARS-CoV-2 spike RBD and how it contacts the ACE2 host cell receptor with notable differences compared to SARS-CoV [54].…”
Section: Discussionmentioning
confidence: 99%